The role of angiogenesis in melanoma: Clinical treatments and future expectations - Wu, Zhuzhu; Bian, Yifei; Chu, Tianjiao; Wang, Yuman; Man, Shuai; Song, Yongmei; Wang, Zhenguo (Frontiers in Pharmacology, 2022)
Skin cancer incidence has been rapidly growing over the last decades, and melanoma is very aggressive and has a high mortality rate, more than 75 percent of all skin cancers. High metastatic potential of melanoma is an essential factor in its high mortality. Various studies have shown the vascular angiogenic system to be crucial for metastasis in melanoma, and its prevention will ultimately inhibit the progression of melanoma. The in-depth understanding of angiogenesis will be of great benefit for melanoma treatment and may promote the development of melanoma therapies. This review aims to summarize the recent advances and challenges of anti-angiogenic agents, including monoclonal antibodies (Bevacizumab, Ramucirumab), tyrosine kinase inhibitors (Sorafenib, Apatinib, Pazopanib, and Regorafenib) and human recombinant endostatin (Endostar). We hope to provide a better understanding of the mechanisms, clinical research progress and future research directions of melanoma.